Pengaruh Kepemimpinan Transformasional dan Motivasi Terhadap Produktivitas Kerja Karyawan Pada PT. Bintang Sewu Sejahtera di Manado - Arsyad, Ashar; Siwi, Max; Sumampouw, Harry (JURNAL ADMINISTRASI BISNIS (JAB), 2015)
ABSTRACT : The company always strives for the employee to provide work productivity as much aspossible so that corporate objectives can be achieved in accordance with the targets set. But it is oftensubjected to various kinds of obstacles because employees have thoughts, feelings, status, desire anddiverse backgrounds are brought into the company. It is necessary for the role of transformationalleadership that can give consideration and the intellectual stimulation individualized and who hascharisma and knowledge about what is the motivation of the employees as motivation from within andfrom outside so that work productivity can be improved. This research was conducted with the aim todetermine the effect of transformational leadership and motivation towards employee productivity byusing the transformational leadership theory of Bass and Avolio, motivation theory of FrederickHerzberg's and the work productivity theory of Sedarmayanti. The method used in this research usingquantitative descriptive, with approach multiple linear regression and multiple linear correlationanalysis. From the research obtainable equation as follows: Y = 2,237 + 0,246 + 0,720 . Theseresults indicate if there is no transformational leadership and motivation in the company, then theemployee productivity is 2,237. If the transformational leadership increased 1 scale on respondents'answers it will increase employee productivity by 0,246. If the motivation to increase by 1 scale on therespondent's answer then the employee's productivity will also increase by 0,720. From the result of Ftestobtained value by 46,873 more than the value of is 3,25 with a significant level 0,000> 0,05 then Ho is rejected and Ha accepted it means transformational leadership and motivationsignificantly influence employee productivity.Keywords : Transformational Leadership, Motivation, Work Productivity